Hands-on agile software development with JIRA : design and manage software projects using Agile methodology - Harned, David (Packt Publishing, 2018)
Plan, track, and release great software Key Features Learn to create reports and dashboard for effective project management Implement your development strategy in JIRA. Practices to help you manage the issues in the development team Book Description As teams scale in size, project management can get very complicated. One of the best tools to deal with this kind of problem is JIRA. This book will start by organizing your project requirements and the principles of Agile development to get you started. You will then be introduced to set up a JIRA account and the JIRA ecosystem to help you implement a dashboard for your team's work and issues. You will learn how to manage any issues and bugs that might emerge in the development stage. Going ahead, the book will help you build reports and use them to plan the releases based on the study of the reports. Towards the end, you will come across working with the gathered data and create a dashboard that helps you track the project's development. What you will learn Create your first project (and manage existing projects) in JIRA Manage your board view and backlogs in JIRA Run a Scrum Sprint project in JIRA Create reports (including topic-based reports) Forecast using versions Search for issues with JIRA Query Language (JQL) Execute bulk changes to issues Create custom filters, dashboards, and widgets Create epics, stories, bugs, and tasks Who this book is for This book is for administrators who wants to apply the Agile approach to managing the issues, bugs, and releases in their software development projects using JIRA.